Consumo, digestibilidade dos nutrientes, comportamento ingestivo e balanço de nitrogênio em cordeiros Santa Inês alimentados com resíduo de cervejaria desidratado - Gonçalves, Ana Gláucia Carneiro Melo (2017)
This study was accomplished with the objective to investigate the intake, apparent digestibility of nutrients, feeding behavior and nitrogen balance in Santa Ines lambs fed rations containing dehydrated brewery residue (BDG). Thirty-five male lambs non-castrated with average initial weight of 16.00 ± 1.69 kg, and, approximately, 70 days of age were used. Were adopted a completely randomized design with five treatments and seven replications, consisting the treatments to 0; 20; 40; 60 to 80% of inclusion of BDG in the concentrate portion of the ration. The duration of the experiment was determined by the time required for the mean body weight of the animals of the treatment reached 28 kg, at which all the experimental animals were slaughtered. The intake of dry matter (DM) in g day-1, % PC and g kg0.75 showed decreasing linear effect (P<0.05). The same behavior was observed for consumption of organic matter (OM), mineral matter (MM), crude protein (CP), total carbohydrates (TC) and total digestible nutrients (TDN), expressed in g day-1. However, the intake of neutral detergent fiber (NDF) increased linearly (P <0.05) with the addition of the BDG, when expressed in % PC and g kg-0.75. The apparent digestibility of ether extract (EE), NDF, acid detergent fiber (ADF) showed linear increase (P<0.05). For the variables related to feeding behavior, feed efficiency (g DM h-1), rumination efficiency (gDM h-1 and gNDF h-1) and entertainment showed decreasing linear effect (P<0.05 ), while the rumination time, total chewing time and number of chews presented increasing linear effect on higher levels of BDG in the feed. It was observed linear effect (P<0.05) for N intake, N and fecal N basal endogenous, however the observed decrease did not affect the nitrogen balance (P>0.05). The brewery waste inclusion levels dehydrated in confinement in sheep rations promote reduced consumption and low coefficients of apparent digestibility of nutrients, as well as reduction in power efficiencies and rumination, however, RCD inclusions are not enough to compromise the nitrogen balance. However, adding up to 20% of the combined potion may be recommended depending on the feasibility of acquisition